2004
DOI: 10.1016/j.febslet.2004.06.093
|View full text |Cite
|
Sign up to set email alerts
|

MCAK, a Kin I kinesin, increases the catastrophe frequency of steady‐state HeLa cell microtubules in an ATP‐dependent manner in vitro

Abstract: Mitotic-centromere-associated kinesin (MCAK) is a member of the KIN I (internal motor domain) subfamily of kinesin related proteins. MCAK and its homologues destabilize microtubules both in cells and in vitro. Here, we analyzed the effects of MCAK in the presence and absence of ATP on the dynamic instability behavior of steady state microtubules assembled from purified HeLa cell tubulin. In the presence of ATP, substoichiometric levels of full length MCAK and a segment (A182) consisting of the motor and neck d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 24 publications
(82 reference statements)
5
34
0
Order By: Relevance
“…In the first, both motors directly associate with MTs at the midzone and their absence therefore disrupts midzone organization. Previous reports regarding the functions of kinesin-related motor proteins in midzone and spindle MT organization [19,[60][61][62][63][64] as well as in control of MT dynamics [65][66][67][68][69] support this idea. In addition, we have recently reported that a combination of mutations in kinesin-5 motors disrupts midzone organization and centering [42].…”
Section: Discussionsupporting
confidence: 69%
“…In the first, both motors directly associate with MTs at the midzone and their absence therefore disrupts midzone organization. Previous reports regarding the functions of kinesin-related motor proteins in midzone and spindle MT organization [19,[60][61][62][63][64] as well as in control of MT dynamics [65][66][67][68][69] support this idea. In addition, we have recently reported that a combination of mutations in kinesin-5 motors disrupts midzone organization and centering [42].…”
Section: Discussionsupporting
confidence: 69%
“…[9][10][11] MCAK, the most studied Kinesin-13, can depolymerize stabilized MTs as well as dynamic MTs in vitro. [12][13][14][15][16] Structurally, it is composed of an N-terminal globular domain that functions in subcellular targeting, 9,11,17,18 a class-specific neck and catalytic core that are essential for efficient MT depolymerization activity, 13,14,[19][20][21] and a C-terminal tail that is responsible for dimerization and the regulation of ATPase and depolymerization activity. 13,14,19,22 While the native protein is dimeric, a monomeric truncation consisting of the neck and catalytic core is sufficient for MT depolymerization in vitro and in cells.…”
Section: Introductionmentioning
confidence: 99%
“…MCAK/kif2c, the best characterized member of the Kin I subfamily, localizes dynamically at various mitotic structures, such as inner centromeres, outer kinetochores, centrosomes, spindle MTs, MT tips, and the spindle midzone (8, 14 -17). MCAK promotes catastrophe of both stable and dynamic MTs via depolymerizing MTs at both ends in vitro (3,18,19). Loss of MCAK function leads to extremely long spindle MTs, although overexpression of MCAK results in a short spindle in vivo (8,20).…”
mentioning
confidence: 99%